Shovel Ready : Archaeology and Roosevelt's New Deal for America. - Means, Bernard K. (University of Alabama Press, 1753)
Shovel Ready provides a comprehensive lens through which to view the New Deal period, a fascinating and prolific time in American archaeology. In this collection of diverse essays united by a common theme, Bernard K. Means and his contributors deliver a valuable research tool for practicing archaeologists and historians of archaeology, as well as New Deal scholars in general. To rescue Americans from economic misery and the depths of despair during the Great Depression, President Franklin Delano Roosevelt created several New De.